2018
DOI: 10.3389/fnhum.2018.00067
|View full text |Cite
|
Sign up to set email alerts
|

Yoga Therapy and Polyvagal Theory: The Convergence of Traditional Wisdom and Contemporary Neuroscience for Self-Regulation and Resilience

Abstract: Yoga therapy is a newly emerging, self-regulating complementary and integrative healthcare (CIH) practice. It is growing in its professionalization, recognition and utilization with a demonstrated commitment to setting practice standards, educational and accreditation standards, and promoting research to support its efficacy for various populations and conditions. However, heterogeneity of practice, poor reporting standards, and lack of a broadly accepted understanding of the neurophysiological mechanisms invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
81
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 63 publications
6
81
0
1
Order By: Relevance
“…The powerful priming effect observed when combining cyclic respiration with muscle contraction supports the “bottom‐up” polyvagal theory proposed by Stephen Porges (Sullivan et al, ). This theory hypothesizes that autonomic regulation is possible through interoception (i.e., an awareness of the internal state of the body's systems) and self‐regulatory skills (Gard, Noggle, Park, Vago, & Wilson, ).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…The powerful priming effect observed when combining cyclic respiration with muscle contraction supports the “bottom‐up” polyvagal theory proposed by Stephen Porges (Sullivan et al, ). This theory hypothesizes that autonomic regulation is possible through interoception (i.e., an awareness of the internal state of the body's systems) and self‐regulatory skills (Gard, Noggle, Park, Vago, & Wilson, ).…”
Section: Discussionsupporting
confidence: 73%
“…Recent focus on stress reduction and physiological resiliency has led to further interest in the autonomic nervous system's adaptation to stress. Many popular mind–body practices such as yoga, Tai Chi, and Qigong have been shown to activate the parasympathetic nervous system (Goyal et al, ; Sullivan et al, ; Walther, Lacker, & Ehlert, ). Paced respiration and dynamic tension through rhythmic skeletal muscle contraction are two core components common to yoga, Tai Chi, and Qigong; however, it remains unclear by which mechanisms these training disciplines activate the parasympathetic nervous system.…”
Section: Introductionmentioning
confidence: 99%
“…This includes a thorough assessment of psychosocial factors followed by psychological therapies such as relaxation training, dynamic psychotherapy, yoga, or a combination of these (Levy et al, 2006;Paul & Basude, 2016). The practice of yoga, with emphases on interoceptive and exteroceptive sensory-motor experience, has an intimate link with autonomic state regulation (Sullivan et al, 2018). There is growing evidence that yoga reduces PTSD symptoms (van der Kolk et al, 2014;Price et al, 2017) and may have benefits for treating functional GI disorders in adolescents and adults (for a systematic review see Schumann et al, 2016).…”
Section: Therapies Utilizing Tactile Vocal and Interoceptive Modamentioning
confidence: 99%
“…Yoga is proposed to offer methods for regulation and resilience through the integrated practice of yamas and niyamas (ethical/intentional principles), asana (physical exercises), pranayama (breathing techniques) and meditation [30, 46]. The focus of yoga therapy on cultivating the connection to steadfast joy, eudaimonic well-being, meaning, and purpose highlights an important place for yoga therapy in caring for the ill client.…”
Section: Discussionmentioning
confidence: 99%
“…Mind-body therapies, including yoga, call for simultaneous attention to the body, breathing, attentional and affective regulation and cognition. Previous studies have shown patients utilizing mind-body therapies such as yoga, reported a shift in their experience of negative emotions as well as the development of self-regulatory skills in dealing with pain, emotional regulation and re-appraisal of life situations [30]. Studies indicate that elements of yoga (gentle movement, slow breathing, meditation, and guided imagery) may lead to mental relaxation and influence aspects of the parasympathetic nervous system associated with a body when at rest [3136].…”
Section: Introductionmentioning
confidence: 99%